Pemberdayaan Ekonomi dan Kewirausahaan Melalui Pemasaran Digital serta Manajemen Lingkungan Sehat di Desa Sungai Raya - Stefani; Heriyadi; Sinta Amanda Putri; Nurul Fadillah; Elika Rani (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Economic empowerment of residents in Sungai Raya Village is focused on business development through digital marketing and healthy environmental management. This activity was carried out by Tanjungpura University students through Student Work Lectures (KKM). Through digital-based entrepreneurial economic empowerment, people receive training to develop businesses by utilizing online marketing technology. The result of this activity is to provide an understanding of entrepreneurship and provide a broader contribution to society. Apart from that, an entrepreneurship workshop was also held for students at SMA Negeri 1 Sungai Raya. In this workshop, students receive training on the basics of entrepreneurship. This activity aims to foster an entrepreneurial spirit among students so that they are ready to face challenges in the business world. This program also includes education about the importance of maintaining a clean environment and good waste management. The community is taught to sort organic and non-organic waste, by providing appropriate trash bins to create a clean and healthy environment. With this approach, Sungai Raya Village is expected to become an example for other villages in integrating digital technology and environmental sustainability for shared prosperity.